PENGARUH PEMENUHAN NUTRISI DAN TINGKAT KECEMASAN TERHADAP PENGELUARAN ASI DESA SUMBER REMBANG - Puji Hastuti; Irfana Tri Wijayanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2017)
ABSTRACT Breastfeeding of infants is expected to achieve the achievement of the 3rd Sustainable De- velopment Goals (SDGs) target of the 2nd targets, namely by 2030 ending infant and toddler mortality up to 12 per 1,000 live births. The smoothness of breast milk production is influenced by many factors such as frequency of breastfeeding, birth weight, gestational age at birth, ma- ternal age and parity, stress and acute illness, IMD, presence of smokers, alcohol consumption, breast care, use of contraceptives, and nutritional status. Quantitative Research Methods that aims to obtain know the influence of nutritional fulfillment and anxiety level of breastfeeding expenditure during childbirth in Rembang district. Object were collected using questionnaire. Results: The fulfillment of nutrition in postpartum mother in the village Source of sufficient category 53,3% and 46,7% is not fulfilled. Anxiety of mother of medium anxious category is56,7% and 43,3% mild anxiety. The smooth expenditure of breast milk 53.3% and 46.7% of milk is not smooth. The result of spearman rho test between the fulfillment of nutri to the expenditure of milk in get p value = 0,01 (0,05) which mean Ha accepted and Ho is rejected that there is influence of nutrition fulfillment with expenditure of ASI in Sumber Village,Rembang district. While spearman rho test between the anxiety level to the expenditure of breast milk obtained p value = 0,01 (0,05) which means there is influence of anxiety level with expenditure of ASI in Sumber Village, Rembang district. Keywords: Nutrition, Anxiety Level and Breastfeeding ABSTRAK Pemberian ASI pada bayi diharapkan mampu untuk mewujudkan pencapaian target Sus- tainable Development Goals (SDGs) ke-3 target ke-2 yaitu pada tahun 2030 mengakhiri kema- tian bayi dan balita hingga 12 per 1.000 kelahiran hidup. Kelancaran produksi ASI dipengaruhi oleh banyak faktor seperti, frekuensi pemberian ASI, berat bayi saat lahir, usia kehamilan saat bayi lahir, usia ibu dan paritas, stres dan penyakit akut, IMD, keberadaan perokok, konsumsi alkohol, perawatan payudara, penggunaan alat kontrasepsi, dan status gizi. Metode penelitian menggunakan kuantitatif yang bertujuan untuk mendapatkan mengetahui pengaruh pemenu- han nutrisi dan tingkat kecemasan terhadap pengeluaran ASI pada masa nifas di Kecamatan Sumber Kabupaten Rembang. Data diambil dengan menggunakan kuesioner. Hasil Penelitian: Pemenuhan nutrisi pada ibu nifas di desa Sumber kategori tercukupi 53,3% dan 46,7% tidak tercukupi. Kecemasan ibu kategori cemas sedang 56,7% dan 43,3% cemas ringan. Kelancaranpengeluaran ASI 53,3% lancar dan 46,7% ASI tidak lancar. Hasil uji spearman rho antara pemenuhan nutri terhadap pengeluaran ASI di dapatkan p value = 0,01 ( 0,05) yang berati Ha diterima dan Ho ditolak bahwa ada pengaruh pemenuhan nutrisi dengan pengeluaran ASI di Desa Sumber Kecamatan Sumber Kabupaten Rembang. Sedangkan uji spearman rho antara tingkat kecemasan terhadap pengeluarana ASI didapatkan hasil p value =0,01 ( 0,05) yang artinya ada pengaruh Tingkat Kecemasan dengan Pengeluaran ASI di Desa Sumber Kecama- tan Sumber Kabupaten Rembang. Kata kunci: Nutrisi, Tingkat Kecemasan dan Pengeluaran ASI